2020
DOI: 10.1111/iwj.13318
|View full text |Cite
|
Sign up to set email alerts
|

Human amniotic membrane allograft, a novel treatment for chronic diabetic foot ulcers: A systematic review and meta‐analysis of randomised controlled trials

Abstract: To evaluate the efficacy and safety of human amniotic membrane (HAM) allograft in treating chronic diabetic foot ulcers (DFUs), a comprehensive search of randomised controlled trials in MEDLINE, EMBASE, PubMed, CENTRAL and Web of Science was conducted to December 7, 2019. Two reviewers independently screened the studies, extracted data, and evaluated the quality of studies. The primary outcome was the proportion of complete healing. The secondary outcomes were mean time to complete healing and adverse events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 25 publications
0
15
0
1
Order By: Relevance
“…Additional comparative effectiveness studies with different materials and bigger groups of chronic wounds of various origin would be beneficial to specify more accurate indications and timing for Amnioderm® application. As part of the use of AM or AM + chorion in patients with DFUs, two meta-analyses were also published that summarized efficacy and safety (Su et al, 2020 ). In Huang et al, a total of nine randomized controlled trials (RCTs) with a total of 541 patients are included.…”
Section: Discussionmentioning
confidence: 99%
“…Additional comparative effectiveness studies with different materials and bigger groups of chronic wounds of various origin would be beneficial to specify more accurate indications and timing for Amnioderm® application. As part of the use of AM or AM + chorion in patients with DFUs, two meta-analyses were also published that summarized efficacy and safety (Su et al, 2020 ). In Huang et al, a total of nine randomized controlled trials (RCTs) with a total of 541 patients are included.…”
Section: Discussionmentioning
confidence: 99%
“…According to a systematic review and meta-analysis study, the safety and efficiency of AAM have been confirmed in the treatment of split-thickness skin graft donor sites [57]. For chronic diabetic foot ulcers, a shorter time to complete healing and a higher proportion of complete healing were observed in the AAM group when compared with the standard wound care group [58].…”
Section: Acellular Amniotic Membrane (Aam)mentioning
confidence: 98%
“…70 A recent meta-analysis including 465 participants showed that there was a 2-fold higher probability of complete wound healing at 12 weeks for patients who received human amniotic membrane plus standard of care in comparison with those receiving only standard of care and also a significantly shorter time to healing (about 30 days). 71 Moreover, some RCTs showed higher probability of wound healing for patients receiving human amniotic membrane products when compared with bioengineered skin substitutes. 72,73 However, 2 retrospective analyses of real world data did not confirm these findings and instead showed superiority of bioengineered skin substitutes.…”
Section: Adjunct Therapiesmentioning
confidence: 99%